(2x-3)(x+1)=0 Then let each factor equal to 0 to solve for x
2x-3=0 and x+1=0
2x=3 x= -1
The equation is solved by factoring
x=7 or x=-7
First you can take a x out of the whole equation:
Then solve for the solutions:
x = - 7, x = 0, x = 7
x³ - 49x = 0 ← factor out x from each term
x(x² - 49) = 0 ← x² - 49 is a difference of squares, thus
x(x - 7)(x + 7) = 0
Equate each factor to zero and solve for x
x = 0
x - 7 = 0 ⇒ x = 7
x + 7 = 0 ⇒ x = - 7
X=3Step-by-step explanation:3X+9=18collect like terms: 3X=18-93X=9divide both side of the equation by 33X/3=9/3X=3
Factor the equation completely.
Set each factor equal to zero, and solve.
List each solution from Step 3 as a solution to the original equation.